(untitled) (Clinics, 2017)
OBJECTIVES: To analyze the motor development of late preterm newborn infants (LPI) from birth to term-corrected age using the Test of Infant Motor Performance (TIMP) and to compare the obtained results with those of term infants at birth. METHODS: Prospective cohort study, 29 late preterm newborn infants were evaluated by the TIMP at birth and every two weeks until term-corrected age. The TIMP was administered to 88 term infants at birth. RESULTS: The mean TIMP score of late preterm newborn infants was 51.9±5.8 at 34–35 weeks and 62.6±5.2 at 40 weeks. There was a significant increase at 38–39 weeks in the LPI group (p